A study of the impact of spatial resolution on the estimation of particle matter concentration from the aerosol optical depth retrieved from satellite observations. Issue 18 (17th September 2019) - Mei, Linlu; Strandgren, Johan; Rozanov, Vladimir; Vountas, Marco; Burrows, John P.; Wang, Yujie
ABSTRACT: The relationship between satellite-derived aerosol optical depth (AOD) and ground-based near-surface particle matter concentration (PM2.5 ) has been investigated with respect to spatial resolution of satellite observations. AOD data product with spatial resolution of 1 km provided by the Multi-Angle Implementation of Atmospheric Correction (MAIAC) using the Moderate Resolution Imaging Spectroradiometer (MODIS) together with PM2.5 data measured by 946 Environmental Protection Agency (EPA) ground monitoring sites across the contiguous US have been used to study the linear relationship between AOD and PM2.5 concentration at different spatial resolutions (1, 3, and 10 km), which is named the AOD spatial resolution effect in the manuscript, for different spatial scales (urban scale, mesoscale, and continental scale). In addition, auxiliary data sets such as meteorological conditions, aerosol properties, and surface characteristics have been analysed to study the impact on the determination of PM2.5 concentration. The conclusions are (1) for both urban, meso-, and continental scale, the correlation between PM2.5 and AOD increases significantly with the increase of AOD spatial resolution; (2) the correlation between AOD and near-surface PM2.5 concentration decreases significantly as the scale of study region increases for the eastern part of the US but the opposite for the western part of the US; (3) the correlation between PM2.5 and AOD is more stable and higher over the eastern part of the US.